Negative Regulation of Ros Receptor Tyrosine Kinase Signaling: An Epithelial Function of the Sh2 Domain Protein Tyrosine Phosphatase Shp-1 - Keilhack, Heike (The Rockefeller University Press, 2001)
Male “viable motheaten” (me(v)) mice, with a naturally occurring mutation in the gene of the SH2 domain protein tyrosine phosphatase SHP-1, are sterile. Known defects in sperm maturation in these mice correlate with an impaired differentiation of the epididymis, which has similarities to the phenotype of mice with a targeted inactivation of the Ros receptor tyrosine kinase. Ros and SHP-1 are coexpressed in epididymal epithelium, and elevated phosphorylation of Ros in the epididymis of me(v) mice suggests that Ros signaling is under control of SHP-1 in vivo. Phosphorylated Ros strongly and directly associates with SHP-1 in yeast two-hybrid, glutathione S-transferase pull-down, and coimmunoprecipitation experiments. Strong binding of SHP-1 to Ros is selective compared to six other receptor tyrosine kinases. The interaction is mediated by the SHP-1 NH(2)-terminal SH2 domain and Ros phosphotyrosine 2267. Overexpression of SHP-1 results in Ros dephosphorylation and effectively downregulates Ros-dependent proliferation and transformation. We propose that SHP-1 is an important downstream regulator of Ros signaling.